Mapping the Chinese and Islamic Worlds : Cross-Cultural Exchange in Pre-Modern Asia. - Park, Hyunhee (Cambridge University Press, 2012)
This book documents the relationship and wisdom of Asian cartographers in the Islamic and Chinese worlds before the Europeans arrived.